2018
DOI: 10.2174/1381612824666180116163411
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and Paraprobiotics in Viral Infection: Clinical Application and Effects on the Innate and Acquired Immune Systems

Abstract: Recently, the risk of viral infection has dramatically increased owing to changes in human ecology such as global warming and an increased geographical movement of people and goods. Howev-er, the efficacy of vaccines and remedies for infectious diseases is limited by the high mutation rates of viruses, especially, RNA viruses. Here, we comprehensively review the effectiveness of several probiot-ics and paraprobiotics (sterilized probiotics) for the prevention or treatment of virally-induced infectious diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
128
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(139 citation statements)
references
References 73 publications
0
128
0
11
Order By: Relevance
“…Recently, new terms such as postbiotics, paraprobiotics, metabiotics, proteobiotics, pharmabiotics, and ghost probiotics have emerged [ 20 , 21 , 22 , 23 , 24 , 25 ]. Interestingly, evidence from the literature suggests that by using the term postbiotics, one refers to either inactivated probiotic strains or their metabolic products or both.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, new terms such as postbiotics, paraprobiotics, metabiotics, proteobiotics, pharmabiotics, and ghost probiotics have emerged [ 20 , 21 , 22 , 23 , 24 , 25 ]. Interestingly, evidence from the literature suggests that by using the term postbiotics, one refers to either inactivated probiotic strains or their metabolic products or both.…”
Section: Introductionmentioning
confidence: 99%
“…Lactic acid bacteria (LAB) have been traditionally used in the production of fermented foods, such as yogurt and cheese, and are regarded as highly safe food materials. It is reported that LAB have many health functions, such as the regulation of intestinal cells, immune cells and microbiota, and they have been used in the production of many functional health foods [1] [2]. We previously found that Lactococcus lactis strain Plasma (LC-Plasma), which is a synonym of Lactococcus lactis subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics means a living micro-organisms that allow a health benefit to the host, including the gastrointestinal tract, when administered in a suitable amount which stimulate immune response by increasing the antibody production [51,52].…”
Section: Prophylaxis and Treatment Of Covid-19mentioning
confidence: 99%